Genome-wide identification and expression analysis of the BAHD gene family in Leonurus japonicus - Wang, Qing; Guo, Tongtong; Yi, Yuxiao; Zhang, Jiaxin; Lv, Wenhan; Yang, Fengtang; Xu, Jianing (Frontiers in Genetics, 2024)
Acylation represents a pivotal biochemical process that is instrumental in the modification of secondary metabolites throughout the growth and developmental stages of plants. The BAHD acyltransferase family within the plant kingdom predominantly utilizes coenzyme A thioester as the acyl donor, while employing alcohol or amine compounds as the acceptor substrates to facilitate acylation reactions. Using bioinformatics approaches, the LjBAHD gene family members in the genome of Leonurus japonicus (L. japonicus) were identified and characterized including gene structure, conserved motifs, cis-acting elements, and potential gene functions. To elucidate the roles of BAHD genes in various tissues of L. japonicus, the expression profiles of LjBAHD family members across different organs were scrutinized. Under drought stress treatment, some LjBAHDs were upregulation, suggesting their potential involvement in drought response. Notably, a detailed study was conducted on a specific HCT gene (i.e., LjBAHD25) within the BAHD gene family. Analysis of its expression patterns suggested a role for LjBAHD25 in the phenylpropanoid metabolism pathway in L. japonicus, contributing to the biosynthesis of secondary metabolites with unique bioactivity. The findings of this study have established a scientific foundation for the subsequent development and functional validation of the BAHD gene family in L. japonicus.